2000
DOI: 10.1366/0003702001949735
|View full text |Cite
|
Sign up to set email alerts
|

Spectral Comparison of the Binding of Pyrene to β-Cyclodextrin and β-Cyclodextrin Derivatives

Abstract: β-Cyclodextrin (β-CD) is a seven-unit cyclic sugar molecule with a torroidal shape, a hydrophilic exterior, and a hydrophobic cavity. It has been hypothesized that pyrene (P) forms a P(β-CD)2 complex in which the pyrene lies in between the two wide, or secondary, rims of the two β-CDs. This dimer structure appears to be stabilized in the crystal state by hydrogen bonds between –OH groups on the rims of the adjacent β-CDs. We have chosen to test this hypothesis by comparing the fluorescence properties of pyrene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2002
2002
2008
2008

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 19 publications
0
8
0
Order By: Relevance
“…[24] The pyrene fluorescence spectrum exhibits five major vibronic bands. There is an intensification of band I relative to band III in polar solvents due to the reduction of the local symmetry of pyrene.…”
Section: Micelle-mimetic Properties Of the Chiral [322]-ionenesmentioning
confidence: 99%
“…[24] The pyrene fluorescence spectrum exhibits five major vibronic bands. There is an intensification of band I relative to band III in polar solvents due to the reduction of the local symmetry of pyrene.…”
Section: Micelle-mimetic Properties Of the Chiral [322]-ionenesmentioning
confidence: 99%
“…The interest in the host–guest relationship of these complexes lies in the fact that they possess a large field of actual and potential applications. For example, they can increase the solubility of organic compounds in water; they can produce better analytical separation through the formation of host–guest complexes between the analyte and the CD; and they are used for drug inclusion as a way to better deliver these 9, 21. Examples of this are the non‐steroidal anti‐inflammatory drug nimesulfide‐cyclodextrin, whose formulations are commercially available, resulting in a faster action of its analgesic action 19.…”
Section: Introductionmentioning
confidence: 99%
“…In the case of the pyrene molecule it is known that inclusion into the inner cavity of CD occurs and this can be followed by the promoted changes in its fluorescence spectra ( I E / I M ratio) and lifetimes 7, 2–15. In fact, the pyrene molecules form a 1:1 inclusion complex with cycloheptaamilose (β‐CD) that only displays the monomer pyrene fluorescence, whereas in the case of γ‐CD (which possesses a larger inner cavity diameter) two pyrene units are able to go inside the CD cavity forming a 1:2 (γ‐CD/pyrene) inclusion complex with consequent excimer emission 10, 14, 15, 21. So far, no interaction studies have been carried out on dye‐labelled polymers and CD.…”
Section: Introductionmentioning
confidence: 99%
“…Of three well-known industrially produced CDs, low-cost p-CD has been further chemically modified. Much attention has been paid to improve its solubility for the purpose of studying the physical properties of inclusion complexes of p-CD with functionalized compounds [7][8][9][10] or to synthesize functionalized p-CD for the purpose of molecular recognition [11][12][13][14]. However, substitution of hydroxyl groups at the rim of p-CD may affect the inclusion of the p-CD host with guests in the above-mentioned areas to a significant extent on the basis of dimensional and hydrophobic considerations.…”
Section: Introductionmentioning
confidence: 99%
“…However, substitution of hydroxyl groups at the rim of p-CD may affect the inclusion of the p-CD host with guests in the above-mentioned areas to a significant extent on the basis of dimensional and hydrophobic considerations. A few groups have reported that modified p-CD shows different hydrogen bonding interactions and thermodynamic parameters [8,9,12]. Little description was presented on steric considerations during the course of inclusion of guests, especially the second guest in the CD cavity.…”
Section: Introductionmentioning
confidence: 99%